Profiles of Average Flow Velocity of Polar Solvent and Unprocessed Hydrocarbon in a Single Stage Symmetrical Bifurcated Channel - Chijioke A. Egbo; Tamunoimi M. Abbey; Ogiosobo D. Opuene; Kiinebari F. Nama; Olushola S. Taiwo; Oladapo M. Olumide; Princess B. Onwe; Amaech O. Azi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Flow distribution is a central subject in the processing industry, petroleum and industry, power industry amongst others. The concept of bifurcation has played key roles towards the realization of this science and engineering concept, as the application of bifurcation is identified in the human physiological system as it appears in the arterial system where it aids the distribution of blood plasma through the human system. In this study and experimental methos is used to ascertain the flow profile of water and crude oil representing polar solvent and unprocessed hydrocarbon, as they are allowed to flow through a bifurcated pipe with 10o, 20o, 30o, 40o, 50o, and 60o angles of bifurcation and a recovery volume of 100ml, 200ml, 300ml, 400ml and 500ml. The velocity profile obtained from this study has revealed the existence of a velocity range in the branched daughter channels of a symmetrical bifurcation, and the velocity range has its maximum and minimum values at the inner and outer walls of the branched daughter bifurcated channels, and the results further reveals the alternation of the maximum velocity between the inner and outer walls of the bifurcated daughter channels.